Writing an invited commentary - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
An invited commentary is a short article that describes an author's personal experience of a specific topic. Unlike a review article, the author gives his own opinions and perspectives. It typically addresses a current, hot and often controversial subject. It may take two formats, namely, provide an expert author's personal views of and insight into a current hot topic, or add balance to another paper being commented upon, with addition of the author's own perspective.